PENGEMBANGAN E-JOBSHEET FOTOGRAMETRI UDARA MENGGUNAKAN DRONE PADA ELEMEN PENGINDERAAN JAUH PROGRAM KEAHLIAN TEKNIK GEOMATIKA DI SMK NEGERI 1 PERCUT SEI TUAN - Satrio Zaidan Faiz Ananda; Zulkifli Matondang; Riansyah Putra; Wisnu Prayogo (STKIP Subang, 2026)
This study aimed to develop an Aerial Photogrammetry E-Jobsheet Using Drone on the Remote Sensing Element of the Geomatics Engineering Expertise Program at SMK Negeri 1 Percut Sei Tuan and to determine its feasibility and practicality. This study used the Research and Development (R&D) method with the 3D model, consisting of Define, Design, and Develop. The product was developed as a GlideApps-based web app containing materials, occupational safety guidance, practical procedures, checklists, evaluation, and reflection. Data were collected through media expert validation, material expert validation, teacher response questionnaires, and student response questionnaires. The results showed that media expert validation obtained 82.69% in the very feasible category, material expert validation obtained 73.56% in the feasible category, teacher responses obtained 79.35% in the practical category, and student responses obtained 78.04% in the practical category. Therefore, the E-Jobsheet was feasible and practical to use as a supporting learning medium.